Awesome Sauce : Create Videos to Inspire Students, Engage Parents and Save You Time - Stock, Joshua (Book collections on Project MUSE., 2020)
"The ability to use video to communicate has become a basic element of literacy - inside and outside the classroom. This playful, fun-to-read book by award-winning educator Josh Stock shows educators how to make simple videos that explain assignments, welcome students to new schools and grades, differentiate lessons for a range of learning levels and more. The book also helps teachers use video to address common issues like enhancing classroom culture and managing parent communication. Structured like a cookbook, Awesome Sauce discusses both the "why" and the "how" behind the strategies. Each section begins with the story of why Stock uses the strategy, demonstrating what teachers will get out of trying it with their students. These explanations are followed by "how-to" recipes that guide readers in creating the "awesome sauce" their videos will become"--